Analysis of The Influence of Social Media Use and Social Behavior of Millennial and Z Generations on The Growth of Tourism Industry - Maksimilianus Gai, Ardiyanto; Silvia Ekasari; Ratnawita; Aglis Andhita Hatmawan; Ita Nurcholifah (Jurnal Sistim Informasi dan Teknologi, 2024)
This study aims to determine how tourism relates to millennials and Z generations by analyzing their motivations for travel experiences and social media use. This study employs a hybrid methodology, primarily focusing on qualitative aspects. We conducted a bibliographic review and descriptive survey analysis by collecting data from 100 respondents through an online survey using Google Forms. The results of the analysis show that millennials and Z generations are highly dependent on smartphones to connect to the internet and social media, with Instagram as the main platform. They spend six to nine hours per day online, and their phones are often considered an extension of themselves. Millennials and Z generations tend to publish their travel photos on Instagram, focusing on experiences that feature stunning natural scenery and expressions of joy, to strengthen their positive image. Millennials and Z generations primarily travel to explore new cultures and interact with people, and their inclination to capture and share photos serves as a social status indicator. Overall, millennials and Z generations use social media as a tool to build and communicate their social identity, focusing on experiences that can strengthen their positive image and gain recognition. Thus, this phenomenon reflects a shift in the way millennials and Z generations interact with the world and seek to influence and inspire others through the digital content they share